Shear thinning in monoclonal antibodies - Paudel, Subhash (Kansas State University, 2016)
Antibodies are large Y-shaped proteins which are used by immune system to identify and neutralize pathogens. Monoclonal antibody therapy is used to treat different patient conditions. There are problems associated with the manufacturability and deliverability of mAb solutions due to the viscous nature of the protein. The viscosity of antibody solutions increases with the increase in concentration and decreases with applied shear. We want to know why these behaviours are seen and to address this problem we have developed a theory describing the rapid viscosity increase with increasing concentration. We use the polymer theory to explain this behaviour. Here antibodies are treated as polymers. The length of the polymer depend on the aggregation. The reptation time increases approximately as the cubic power of size of aggregate (N³ ). We see the shear thinning behaviour is dependent on the Ab-Ab binding energy and find the relationship between the size of the aggregate and the binding energy. We find aggregate size and morphology using several models for Ab-Ab interaction sites. We use the head to head binding (fAb-fAb binding) model to describe aggregation state in our viscosity theory. The size of the aggregate and hence the reptation time is captured by the binding energy. When the binding energy increases the zero shear viscosity increases and the reptation time decreases. Likewise when the binding energy decreases the zero shear viscosity decreases and the reptation time increases. We have yet to find the correct exponents for the shear thinning behaviour of different mAbs which would be our future work.
Keywords: Shear thinning in mAbs